Effects of the Vibrational Motion of XHY–ON the Post-Photo Detachment Dissociation Dynamics of the XHY Complex (X, Y = Br, I) - Ocampo-Restrepo, Vivianne K.; Arce, Julio C.; López, José G. (Revista de Ciencias, 2013)
We explore the effects of the transition-state vibrational motions on the dynamics of the reaction X + HY →[XHY]‡→XH + Y with X and Y = Br, I. We performed simulations of the dissociation process of the unstable XHY complex using a classical trajectory methodology, combined with London-Eyring-Polanyi-Sato (LEPS) potentials to approximate the interactions among the atoms in XHY. We employed an almost classical sampling scheme on the stable XHY–species to obtain the initial conditions for the trajectories by assuming a vertical transition to the XHY neutral potential energy surface. To study the effects of the vibrations, we considered different sets of initial conditions reflecting specific XHY normal mode excitations. We found an increase in the rotational energies of the product diatoms with an increase in the energy associated to the bending normal modes of XHY. Analysis of the vibrational distributions of the diatoms shows higher most probable vibrational quantum numbers for HBr when compared to HI. For some initial conditions, we also found approximately thermal rotational distributions in the product diatoms.